PENDIDIKAN ETIKA DAN GENDER DALAM TEKS SATUA I TUUNG KUNING - Ida Bagus Gede Paramita (Jurnal Inovasi Penelitian, 2020)
Gender inequity occurs in various aspects of life, including literary works. One of the literary works that describe inequity towards women is Satua I Tuung Kuning. Inequity towards women reflected in the satua I Tuung Kuning is a discrimination against women in a family. Women was put in the second position in a family. Husband could not fulfill his obligations as a good husband in the household. The reason is that patriarchal culture has a strong basic in the social construction become unfair in giving women opportunities. Women also lack awareness to improve their quality.